Automatic modulation format/bit-rate classification and signal-to-noise ratio estimation using asynchronous delay-tap sampling. (October 2015) - Khan, Faisal Nadeem; Teow, Chiew Hoon; Kiu, Shiu Guong; Tan, Ming Chieng; Zhou, Yudi; Al-Arashi, Waled Hussein; Lau, Alan Pak Tao; Lu, Chao
Highlights: A technique for joint modulation format and bit-rate classification is proposed. The proposed technique can simultaneously enable non-data-aided SNR estimation. The technique uses asynchronous delay-tap plots with artificial neural networks. The signal classification accuracy is 99.12% and mean SNR estimation error is 0.88 dB. Due to its simplicity, it is attractive for future cognitive wireless networks. Abstract: We propose a novel technique for automatic classification of modulation formats/bit-rates of digitally modulated signals as well as non-data-aided (NDA) estimation of signal-to-noise ratio (SNR) in wireless networks. The proposed technique exploits modulation format, bit-rate, and SNR sensitive features of asynchronous delay-tap plots (ADTPs) for the joint estimation of these parameters. Simulation results validate successful classification of three commonly-used modulation formats at two different bit-rates with an overall accuracy of 99.12%. Similarly, in-service estimation of SNR in the range of 0−30 dB is demonstrated with mean estimation error of 0.88 dB. The proposed technique requires low-speed asynchronous sampling of signal envelope and hence, it can enable simple and cost-effective joint modulation format/bit-rate classification and NDA SNR estimation in future wireless networks. Graphical abstract: